Ethnicization and identity construction in Malaysia - Holst, Frederik (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2012)
Provide[s] an in-depth and multifaceted study of the processes of ethnicization and identity construction in Malaysia, from the colonial period until the present
Includes bibliographical references and index.
Keywords: Ethnicity -- Malaysia; Malaysians -- Ethnic identity; Malaysia -- Ethnic relations